2017
DOI: 10.1037/pspp0000093
|View full text |Cite
|
Sign up to set email alerts
|

Puffed-up but shaky selves: State self-esteem level and variability in narcissists.

Abstract: Different theoretical conceptualizations characterize grandiose narcissists by high, yet fragile self-esteem. Empirical evidence, however, has been inconsistent, particularly regarding the relationship between narcissism and self-esteem fragility (i.e., self-esteem variability). Here, we aim at unraveling this inconsistency by disentangling the effects of two theoretically distinct facets of narcissism (i.e., admiration and rivalry) on the two aspects of state self-esteem (i.e., level and variability). We repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
140
3
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(173 citation statements)
references
References 105 publications
19
140
3
2
Order By: Relevance
“…However, subsequent research suggested that the grandiosity scale had a different pattern of correlation than other narcissism instruments emphasizing grandiosity (Miller et al, ; Miller, Lynam, & Campbell, ) and that the vulnerability construct was empirically similar to neuroticism, which raised concerns about discriminating narcissistic and borderline PDs (Miller et al, ). This attention to the multidimensionality of narcissism was associated with a variety of interesting programs of research on the measurement (Back et al, ; Glover, Miller, Lynam, Crego, & Widiger, ; Roche, Pincus, Lukowitsky, Menard, & Conroy, ), correlates (Miller, Lynam, Hyatt, & Campbell, in press; Morf et al, in press), and dynamics of narcissism (Back et al, ; Geukes et al, ; Leckelt, Küfner, Nestler, & Back, ; Lukowitsky & Pincus, ; Roche, Pincus, Conroy, Hyde, & Ram, ). However, so far, no consensus has emerged regarding how the concept is meaningfully distinct from particular patterns of nomothetic traits (Ackerman et al, ).…”
Section: Personality Disorders As Traitsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, subsequent research suggested that the grandiosity scale had a different pattern of correlation than other narcissism instruments emphasizing grandiosity (Miller et al, ; Miller, Lynam, & Campbell, ) and that the vulnerability construct was empirically similar to neuroticism, which raised concerns about discriminating narcissistic and borderline PDs (Miller et al, ). This attention to the multidimensionality of narcissism was associated with a variety of interesting programs of research on the measurement (Back et al, ; Glover, Miller, Lynam, Crego, & Widiger, ; Roche, Pincus, Lukowitsky, Menard, & Conroy, ), correlates (Miller, Lynam, Hyatt, & Campbell, in press; Morf et al, in press), and dynamics of narcissism (Back et al, ; Geukes et al, ; Leckelt, Küfner, Nestler, & Back, ; Lukowitsky & Pincus, ; Roche, Pincus, Conroy, Hyde, & Ram, ). However, so far, no consensus has emerged regarding how the concept is meaningfully distinct from particular patterns of nomothetic traits (Ackerman et al, ).…”
Section: Personality Disorders As Traitsmentioning
confidence: 99%
“…A narrower level of dynamics involves variation from one situation to the next. Studying this level of variation using diaries, smartphones, or automated recording devices has become common in basic (Fleeson, , ; Fournier, Moskowitz, & Zuroff, ; Geukes, Nestler, Hutteman, Dufner, et al, ; Geukes, van Zalk, & Back, ; Moskowitz, Moon‐ho, & Turcotte‐Tremblay, ) and clinical (Ebner‐Priemer et al, ; Roche, Pincus, Rebar, Conroy, & Ram, ; Sadikaj, Moskowitz, & Zuroff, ; Sadikaj, Russell, Moskowitz, & Paris, ; Shiffman, Stone, & Hufford, ; Trull et al, ; Wright et al, ; Wright, Hopwood, & Simms, ; Wright, Scott, Stepp, Hallquist, & Pilkonis, ) research. In clinical psychology, psychotherapists often encourage patients to reflect on the fact that they are different from one situation to the next via comments such as ‘you're talking much less than usual today’ or ‘I have noticed that whenever we have a session in which you get upset, you have a long talk with your wife just afterward’ (Weiner & Bornstein, , p. 205).…”
Section: Personality Disorder Dynamicsmentioning
confidence: 99%
“…Some such research exists, although it has largely focused on self-esteem instability [48][49] or focused solely on grandiosity [50].…”
Section: Moving Forward: Studying Dynamic Within-person Processesmentioning
confidence: 99%
“…However, the NARC models the behavioral dynamics of narcissism as two distinct processes related to perceived opportunities (admiration) or threats (rivalry) to maintaining grandiose self‐views. Supporting this multidimensional perspective, narcissistic admiration and rivalry uniquely predict an array of divergent outcomes, including evaluations of others in relationships (Zeigler‐Hill & Trombly, ), the positivity and stability of self‐views (Geukes et al, ), and interpersonal behaviors (Leckelt, Küfner, Nestler, & Back, ).…”
Section: Introductionmentioning
confidence: 99%